(untitled) (Bangladesh Pharmaceutical Journal, 2017)
The purpose of this study was to explore Lactobacillus species from yogurt and cheese that can be used as potential probiotics. In this study, a total of twenty five samples, fifteen from cheese and ten from yogurt were collected from local markets, Dhaka city during May-July, 2016. Single colonies were isolated by enriching in MRS broth and subsequent streaking on MRS agar plate. Total twenty five isolated bacteria were identified as Lactobacillus species by morphological, gram staining and short biochemical tests. All isolated strains were characterized for probiotic properties including acid and salt tolerance, phenol tolerance, sugar fermentation, lactose fermentation and proteolytic activity. Acid tolerance test was performed at pH 2, 3, 4, 5, 6, 7 and 8 in MRS broth. Results showed all isolates survived in highly acidic pH, however most of the strains also survived in alkaline media (pH 8). Salt tolerance test was performed at 2%, 4% and 8% NaCl in MRS broth. All isolates survived in 2% and 4% NaCl concentrations. Phenol tolerance test was performed in MRS broth with 0.1%, 0.2%, 0.3% and 0.4% phenol concentration. All strains survived in 0.1% and 0.2% phenol concentrations. Sugars such as glucose, fructose, sucrose, xylose and lactose were used for fermentation tests. Results of fermentation test showed that most isolates fermented all sugars. All strains digested casein by producing protease enzyme in skim milk agar plate. This study indicated that Lactobacillus species from yogurt and cheese samples have potential probiotic properties. Further study is needed to find specific probiotics with specific benefit from yogurt and cheese. Bangladesh Pharmaceutical Journal 20(1): 27-33, 2017